End milling of Carbon Fiber Reinforced Plastics as surface pretreatment for adhesive bonding – effect of intralaminar damages and particle residues. Issue 12 (9th September 2020) - de Freese, J.; Holtmannspötter, J.; Raschendorfer, S.; Hofmann, T.
ABSTRACT: In this study, the use of dry end milling of carbon fiber reinforced plastics (CFRP) as surface pretreatment for high-strength (structural) adhesive bonding was investigated. Surfaces were pretreated using different milling parameters; subsequently, they were adhesively bonded and tested. In comparison with sanding and other industrial standard pretreatment methods, the measured adhesive strength was significantly lower. Detailed surface investigations utilizing field-emission scanning electron microscopy could identify two major effects for lower adhesion strength. Intralaminar damages and microparticle residues on the created surface reduced the strength of the CFRP adhesive joints. This eventually explains results from investigations on milling pretreated repairs. By application of power ultrasound cleaning equipment and coating with low viscosity epoxy primers, the authors showed a way to overcome the discovered drawbacks and to improve bond strength significantly. Surface roughness measurements showed that the arithmetical mean roughness Ra can be used as an effective value for assessment of mechanical pretreated CFRP surfaces as well as for the quality of necessarily following cleaning processes.